THE ROLE OF HUMOR IN STYLISTIC VARIATION IN OSCAR WILDE’S "THE IMPORTANCE OF BEING EARNEST" - Ma'ripov Jalolxon Kamoliddin o'g'li; Xidirova Dilnoza Nurali qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Oscar Wilde’s "The Importance of Being Earnest" is a quintessential example of farcical comedy, renowned for its witty dialogue and satirical undertones. This paper examines how humor functions as a key element of stylistic variation within the play. Through a close analysis of techniques such as wordplay, irony, and satire, the study demonstrates how Wilde employs humor to: 1) create distinct character voices and establish social hierarchies; 2) satirize Victorian social conventions and expose underlying hypocrisies; 3) drive the plot forward and enhance dramatic irony; and 4) cultivate a unique aesthetic characterized by wit, elegance, and intellectual playfulness. By dissecting the interplay between humor and style, this paper sheds light on the multifaceted nature of comedic expression and its significance in shaping literary and dramatic art.